Planning Policies and Public Health in Kurdistan Region of Iraq (KRI) and Its Policies to Combat COVID-19 in Duhok City - Taha, Aihan (Journal of Public Policy and Administration, 2024)
Purpose: The Kurdistan region of Iraq had been affect by the covid pandemic like the rest of the part in the world and Duhok city specifically faced several problems as the city and health policy were not ready to ace the crises. It had a negative impact on the sustainability of health sector specifically the economic side. This study tries to identify the problems to achieve tan appropriate standard of good health among Kurdistan's general population, especially in the city of Duhok, to ensure more equitable access to health services throughout the country's social and geographic expansion, take into account poverty and to strive to get better treatment, understand the condition of the city of Duhok via COVID-19, and how the government deals with the medical system in this condition, protect and encourage the right to health care for individuals and create equality in the health care system for both genders, beliefs and positions. Methodology: Through conducting the qualitative research approach by using two types for collecting data ( Data Collection Methods) which are primary data and secondary data, primary data for collecting direct information from patients and IDPs and refugees to know their health conditions and whether they are satisfied or not for public health system, physicians as well to know their treatment to patients, and secondary data to gather information from health directorate in Duhok city, camp health administration and humanitarian health organizations to understand better the situation. Findings: The findings of the study indicates that the pandemic struck at a time when public faith in the government was low, the economy was damaged by lower oil sales income, protests were common across the country, and violent extremist acts were on the rise. COVID-19 has worsened long-standing and sometimes deep-seated political, economic, social, and security issues. The COVID-19 pandemic has resulted in a dramatic loss of human life around the world, posing an unprecedented challenge to public health, food systems, and the workplace. The pandemic's economic and social impact is devastating: tens of millions of people are at risk of falling into extreme poverty, while the number of undernourished people is currently estimated to be nearly 690 million, By the end of the year, the number could have risen to 132 million. Unique Contribution to Theory, Practice and Policy: Food security, public health, and employment and labor issues, particularly worker health and safety, all intersect during the COVID-19 crisis. However, in Azadi hospital we cannot talk to people because of virus, the risk of contracting COVID-19 via an infected person's feces appears to be low. The COVID-19 virus may cause intestinal infection and be found in feces, according to some data.